Faktor-Faktor Yang Berhubungan Dengan Kejadian Picky Eater Pada Anak Usia Toddler - Fertycia, Fadhilah Putri (Jurnal Kesehatan Ilmiah Aufa Royhan, 2022)
Picky eater is a food-choosing behavior characterized by no desire to try new food variants. This study aims to determine the factors associated with the incidence of picky eaters in toddler-age children. This study used a descriptive correlative design with a retrospective approach. The research sample was 113 respondents using the purposive sampling technique. The collection of picky eater data using the CEBQ (Child Eating Behaviour Questionnaire) questionnaire adopted from Herze's study (2014) which is a CEBQ that has been translated into Indonesian and carried out validity and reliability tests using Cronbach"s Alpha. This study used univariate and bivariate analysis with a chi-square statistical test. The results of the analysis show that factors related to the incidence of picky eaters, including the eating behavior of parents with picky eater incidence in toddler-age children (p-value 0.003: α 0.05), parental parenting patterns with picky eater incidence in toddler-age children (p-value 0.013: α 0.05), history of exclusive breastfeeding with picky eater incidence in toddler-age children (p-value 0.000: α 0,05). Parental eating behavior, parenting style, and history of exclusive breastfeeding have a significant relationship with the incidence of picky eaters in toddler-age children. It can be concluded that parental eating behavior, parenting patterns, and history of exclusive breastfeeding have a significant relationship with the incidence of picky eaters in toddler-age children. It is hoped that mothers can maintain child nutrition to avoid picky eaters in toddler-age children.